The Definition of STEM and Key Features of STEM Education Learning Activity - จำรัส สุทธิดา (STOU Education Journal, 2017)
This article is the results of literature review and knowledge synthesis to answer essential questions about the definition of STEM, and the key characteristics of STEM education activity. Clear understanding of STEM definition and practices in term of the integration of science, technology, engineering and mathematics will lead to an effective way promote STEM education. Based on both literature review and experiences in providing academic services of the author, it has been found that key characteristics of STEM Education learning activity consist of 6 features: (1) the integration of science, technology, engineering, and mathematics that addresses STEM literacy; (2) designing learning activities based on learning progression framework; (3) providing context-based learning; (4) emphasizing 21st century learning; (5) organizing activities focusing on designing and problem solving; and (6) employing authentic and formative assessment. The definition and practices of STEM education, including its key features of the learning activities will enable teachers to design and implement STEM education in their classroom. Furthermore, they can be applied in teacher professional development as they help teachers develop capacity in designing and developing STEM activity for their own specific classroom contexts.